The comparative antimicrobial effect of Activated Virgin Coconut Oil (AVCO) and Virgin Coconut Oil (VCO) against dental caries-related pathogens - Haron, Ummi Aqilah; Abllah, Zurainie; Mohamad Nasir, Nur Ainatul Mardia (2018)
The present-day diet is astoundingly cariogenic, owing to the fact that high food intake with plenty of fermentable carbohydrates present in them. Classic regime against dental caries such as fluoride is often not able to cope with the resultant massive cariogenic challenge. Therefore, demands of alternatives for the classic regime in arresting issues related to oral health are always on the increase. In contemplation to improve and further develop novel antimicrobial compound, a great deal of research has gone into optimizing a lot of components presently available in natural sources which may help to contribute to the antimicrobial activity. The virgin coconut oil (VCO) is a case in point and has been the focus for decades as it has proven to possess antimicrobial features on Gram positive bacteria. Recently, there is a patterned Activated Virgin Coconut Oil (AVCO) that reported to have a broad antimicrobial spectrum. However, information regarding the inhibitory of AVCO and VCO against dental caries-related pathogens are yet to be established. In this study, we compared the antimicrobial effect of AVCO obtained from KL trading, Selangor, Malaysia, and VCO extracted in our laboratory. Their MIC and MBC against the selected dental caries-related pathogen; Streptococcus mutans, Lactobacillus casei and Candida albicans were determined. Out of the three tested organisms, L. casei was subjected to have a higher sensitivity towards AVCO (MIC: 0.78 mg/ml and MBC: 1.56mg/ml), followed by C. albicans (MIC: 3.12 mg/ml and MBC: 6.24 mg/ml) and S. mutans (MIC: 6.24 mg/ml and MBC: 24.96 mg/ml). In contrast to a positive finding of AVCO, VCO has shown no inhibitory effect on all tested dental caries-related pathogens. Furthermore, the time killing assay revealed that AVCO showed relatively quick-killing activity at the 8 hours of time for all tested organism. These finding correlates with that of AVCO possess bactericidal activity, thereby allowing the possible classification of the AVCO as being a bactericidal agent.